Developing individual and organisational work-life balance strategies to improve employee health and wellbeing. Issue 3 (7th April 2015) - Zheng, Connie; Molineux, John; Mirshekary, Soheila; Scarparo, Simona
Abstract : Purpose: – Work-life balance (WLB) is an issue of focus for organisations and individuals because individuals benefit from having better health and wellbeing when they have WLB and this, in turn, impacts on organisational productivity and performance. The purpose of this paper is to explore relevant WLB factors contributing to employee health and wellbeing, and to understand the interactive effects of individual WLB strategies and organisational WLB policies/programmes on improving employee health and wellbeing. Design/methodology/approach: – Using the data collected from 700 employees located in Queensland, Australia, multiple regression analysis was conducted to examine the variables related to individual WLB strategies and organisational WLB programmes. Several multiple regression models were used to evaluate interrelated relationships among these variables and their combined effects on employee health and wellbeing. Findings: – The authors found that employees exercising their own WLB strategies showed better health conditions and wellbeing that those who do not; they were also more capable of achieving WLB. Both availability and usage of organisational WLB programmes were found to help employees reduce their stress levels, but interestingly to have no direct association with WLB and employee health. Several control variables such as age, working hours, education level and household incomes were found to have moderate effects on employee health and wellbeing. Originality/value: – Employee health and wellbeing are determined by multiple factors. In distinguishing from prior research in this field, this study discovers an important interface between individual WLB strategies and organisational provision of WLB policies/programmes supplemented by several exogenous factors in addressing overall employee health and wellbeing. The results have implications for organisational delivery of WLB policies and other human resource management practices to support employees.